Characterisation and effect of protectants on preservation of Bacillus methylotrophicus UPMC 1166 isolated from liquid biofertiliser - Mansor, Musliyana; Tan, Geok Hun; Abu Asan, Nor Umaira; Abdul Rahim, Raha (Universiti Putra Malaysia Press, 2018)
UPMC 1166 bacterial strain was isolated from SG1 liquid biofertiliser and has proven to have an ability to produce indole acetic acid (IAA) and fixed atmosphere nitrogen. The objectives of this research were to characterise UPMC 1166 isolate, to determine the growth kinetics, and effect of different protectants for preservation. UPMC 1166 were characterised phenotypically and genotypically. The growth kinetics was determined using viable cell count and optical density methods. The effect of different protectants on the viability of UPMC 1166, subjected to freeze–drying and freezing at −80o C, was studied. UPMC 1166 belonged to Gram-positive bacteria (with the size of 0.49 – 0.52 × 1.56 – 2.34 µm), catalase positive, rod-shaped with the arrangement of single or paired bacilli, endospore forming and creamy white pigmentation colonies. Based on API biochemical test kit confirmed that UPMC 1166 was under the Bacillus genus. From BLAST, UPMC 1166 showed pairwise sequence similarity range of 99.0% and is closely related to Bacillus siamensis, Bacillus amyloliquefaciens, Bacillus vallismortis, Bacillus subtilis, Bacillus mojavensis, and Bacillus atrophaeus. 16S rRNA gene sequence used for phylogenetic tree analysis suggested that UPMC 1166 is Bacillus methylotrophicus. To obtain the maximum viability after preservation, it is important to harvest cells during the late logarithmic phase of growth and to choose a suitable protective agent. UPMC 1166 needs approximately 16 h to reach the end of the logarithmic phase; consisting of a lag phase up to 2 h and the logarithmic growth that lasted up to 14 h before entering the stationary phase. During freeze–drying, the maximum protection for UPMC 1166 was achieved by using 10% skimmed milk with 1% sodium glutamate, and 5% trehalose. Maximum protection of cells during −80o C cryopreservation was achieved with 10% dimethyl sulfoxide (DMSO). A suitable selection of protectant seemed to be important to acquire maximum cells viability for long-term preservation. Resistance potential of bacterial strains toward preservation procedures is useful from a research and commercial point of view.